A prospective, multicenter study of low dose decitabine in adult patients with refractory immune thrombocytopenia. Issue 12 (17th October 2019) - Zhou, Hai; Qin, Ping; Liu, Qiang; Yuan, Chenglu; Hao, Yunliang; Zhang, Haiyan; Wang, Zhencheng; Ran, Xuehong; Chu, Xiaoxia; Yu, Wenzheng; Wang, Xin; Hou, Yu; et al.
Abstract: We conducted a prospective, multicenter study to evaluate the efficacy and safety of low‐dose decitabine in adult patients with refractory immune thrombocytopenia. Adult patients who did not respond to, did not tolerate, or were unwilling to undergo splenectomy, with either a baseline platelet count less than 30 × 10 9 /L or the presence of bleeding symptoms and further need of ITP‐specific treatments, were enrolled. Patients received decitabine at 3.5 mg/m 2 intravenously for three consecutive days per cycle, for three cycles with a four‐week interval between cycles. All patients were assessed every week during the first 12 weeks and at four‐week intervals thereafter. We screened 49 patients for eligibility. Four patients were excluded and 45 received decitabine. At the end of decitabine treatment, complete response was achieved in eight patients (17.78%), and partial response was achieved in 15 patients (33.33%). The median time to initial response was 28 days (range, 14‐70 days). Furthermore, seven relapsed patients received decitabine retreatment and all showed platelet response, including one complete response and six partial responses. Sustained response rates at 6, 12 and 18 months were 44.44% (20/45), 31.11% (14/45) and 20.0% (9/45), respectively. For responders, immune thrombocytopenia‐related symptoms, fatigue, psychological health, fear, and overall quality of life were significantly improved. Adverse events were observed in 13 (28.89%) patients. No serious adverse events were recorded. In conclusion, low dose decitabine is potentially effective and safe in the management of adults with refractory immune thrombocytopenia. This trial is registered with clinicaltrials.gov identifier: NCT01568333.